Applying a social determinants of health perspective to early adolescent cannabis use – An overview. (April 2013) - Hyshka, Elaine
<x xml:space="preserve">Abstract</x> Cannabis is the most widely used illicit drug in the world. Although the risk of problematic cannabis use is relatively low, the lifetime prevalence of dependence is greater than for all other illicit drugs. As such, the population burden of problematic cannabis use warrants attention. Many health and psychosocial risks associated with cannabis use are exacerbated or predicted by initiation of cannabis use in early adolescence and early adolescent users are more vulnerable to negative developmental outcomes, longer cannabis use trajectories, earlier transitions to heavier use and dependence. This suggests a need for effective prevention interventions targeting this age group. Unfortunately, most prevention efforts focus on individual-level risk factors and evidence indicates that they are not particularly effective for deterring use. This overview outlines a more effective approach for preventing cannabis-related harm. Using a social determinants of health perspective, it highlights peer networks and family structure and quality as the main risk factors associated with early adolescent cannabis use. This article suggests that interventions that targeting these determinants can be effective for preventing cannabis use. It concludes by suggesting complementary harm reduction programmes for older adolescents as a means to further reduce cannabis-related harm.